Pengaruh Iklan dan Label Halal terhadap Keputusan Pembelian Produk Kosmetik Wardah (Studi Kasus Mahasiswi Fakultas Dakwah Universitas Kiai Haji Achmad Siddiq Jember) - Huroniyah, Fuadatul; Putri, Afrisa Mulyani (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
Indonesia is a country with the largest Muslim population in the world, so it has great potential for halal products, as evidenced by the increasing number of halal products marketed based on Islamic law. However, a phenomenon that is often encountered is that Muslim consumers pay little attention to the halal label on product packaging. Currently, television advertising which used to be a promotion is now starting to be abandoned and is less popular, as a result consumers are less motivated to buy products. The focus of the problem in this research is: do halal advertising and labels have a partial or simultaneous effect on the decision to purchase Wardah cosmetic products among students at the Faculty of Da'wah, UIN KHAS Jember? This research aims to determine the influence of advertising and halal labels partially or simultaneously on purchasing decisions for Wardah cosmetic products among female students at the Faculty of Da'wah, UIN KHAS Jember. The method used is descriptive quantitative. The population in this study were Islamic Communication and Broadcasting students class of 2020 at UIN KHAS Jember, with a total sample of 63 respondents in this study. The sampling technique in this research is purposive sampling technique. The data analysis technique used is quantitative analysis expressed by numbers and calculations using SPSS. The results of data processing show that the results of the hypothesis test using the t test show that t calculated for advertising is (7.820) > t table (1.999) with a significance value of 0.000 and t calculated for the halal label of (2.064) > t table (1.999) with a significance value of 0.043. is below 0.05, which means that halal advertising and labels partially influence the decision to purchase Wardah cosmetic products among students at the Da'wah Faculty of UIN KHAS Jember, or in other words Ha is accepted and Ho is rejected. Then for the F test, the calculated F was obtained at (65.907) > F table (4.00) with a significant value of (0.000) < (0.05), which means that halal advertising and labels simultaneously influence the decision to purchase Wardah cosmetic products among female students. Faculty of Da'wah UIN KHAS Jember, or in other words Ha was accepted and Ho was rejected. Meanwhile, the magnitude of the influence based on the results of data testing is 0.687, which means that halal advertising and labels can influence the decision to purchase Wardah cosmetic products among students at the Da'wah faculty of UIN KHAS Jember by 69.9%, while the remaining 30.1% is influenced by other variables. which was not examined in this study.